High-Temperature Refrigerated Warehouse Operation under Real-Time Pricing of Electricity - Magoo, Nitin (University of Wisconsin-Madison, 2003)
Refrigerated warehouses play an important link in the storage of food products throughout the year under conditions specially suited to prevent their decay. In doing so, refrigerated warehouses serve as an indispensable link in maintaining the availability of otherwise seasonal food products all year round. A proper humidity and temperature level has to be maintained in the warehouse at all times to make this possible. The operation of the warehouse is an energy intensive process; however, under many electricity pricing tariffs, there are no cost benefits of adopting operating strategies that shift electrical usage to lower price (off-peak) periods, i.e., a demand-shifting strategy. But, with the deregulation of utility rate structures, there has been a gradual shift towards Real- Time Pricing (RTP), whereby the electricity price varies every hour. The RTP rate is a typical example of the demand-supply interaction. The RTP structure offers consumers the incentive of reducing their electricity bill if they can shift their loads from high price to low price periods. The benefit to the end-user is reduced utility operating costs (even with equal or slightly higher energy usage). The utilities benefit by being able to reduce their cost of electricity generation by stimulating stability in their aggregate demand of electricity through pricing signals. It is with these thoughts in mind that this study investigates possible operating cost gains for high-temperature refrigerated warehouses by adopting operating strategies that shifts refrigeration system operation to lower price periods. By utilizing the thermal mass of the stored product, the warehouse refrigeration equipment can be operated in a way that would minimize the energy bill of the warehouse. Demand-shifting involves pre-cooling products stored in the warehouse to lower temperatures during low electricity price periods, and shutting off or operating the refrigerating equipment at reduced capacity during periods of high electricity prices. This strategy offers the possibility of shifting electrical usage from higher price to lower price periods resulting in the potential for realizing operating cost savings. A constraint in this process is the thermal risk to stored products. In all operating scenarios, stored product quality or food safety must not be compromised. The warehouse being investigated in the current study is a high-temperature warehouse, or a "cooler", which means that the storage temperature in the warehouse is above the freezing point. Also, it is a distribution warehouse, which means that the stored products arrive "at-temperature", dwell in the warehouse for a short time and then ship to the market "at-temperature". A computer simulation model for a warehouse located in Madison, WI was developed in TRNSYS. The simulation model includes the construction details of the warehouse as well as models for the refrigeration equipment needed to maintain desired storage temperatures. The infiltration exchange between the warehouse zones, and also between the warehouse and the ambient was modeled. The warehouse set-point temperature controller was developed to operate the refrigeration equipment depending on the time of the day and the maximum allowable product temperature. Two different models were developed for the stored products. The first assumed the product to behave as thermally lumped using a lumped capacitance model. The second discretized the product using a three-dimensional finite difference approach. An economic analysis is performed for three different utility rate structures and the results indicate that following the demand-shifting strategy can lead to savings, without adversely affecting the quality of the stored product. The actual value of savings and the percentage savings depend on the utility rate structure in force.
Under the supervision of Professors Douglas Reindl and Sanford Klein; 156pp.
Keywords: Thesis (M.S.)--University of Wisconsin--Madison, 2003.; Dissertations Academic Mechanical Engineering.; University of Wisconsin--Madison. College of Engineering.